2020
DOI: 10.3389/fimmu.2020.01427
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk From Atopic Mothers Has Lower Levels of Short Chain Fatty Acids

Abstract: Short chain fatty acids (SFCAs) are microbial metabolites produced in the gut upon fermentation of dietary fiber. These metabolites interact with the host immune system and can elicit epigenetic effects. There is evidence to suggest that SCFAs may play a role in the developmental programming of immune disorders and obesity, though evidence in humans remains sparse. Here we have quantified human milk (HM) SCFA levels in an international cohort of atopic and non-atopic mothers (n = 109). Our results demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 44 publications
1
54
0
Order By: Relevance
“…Short chain fatty acids (SCFA), including butyrate, acetate, and propionate, are the result of bacterial metabolism in the maternal gut and may reach the mammary gland through the bloodstream. These metabolites are key players in human homeostasis because of their interactions with the microbiota, the immune system, and the neuroendocrine system, contributing to the immunological, metabolic, and neurological programming of the host (Stinson et al, 2020). In this context, the concentrations of acetate and butyrate in milk samples from atopic mothers are significantly lower than in samples from non-atopic mothers (Stinson et al, 2020).…”
Section: Other Human Milk Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Short chain fatty acids (SCFA), including butyrate, acetate, and propionate, are the result of bacterial metabolism in the maternal gut and may reach the mammary gland through the bloodstream. These metabolites are key players in human homeostasis because of their interactions with the microbiota, the immune system, and the neuroendocrine system, contributing to the immunological, metabolic, and neurological programming of the host (Stinson et al, 2020). In this context, the concentrations of acetate and butyrate in milk samples from atopic mothers are significantly lower than in samples from non-atopic mothers (Stinson et al, 2020).…”
Section: Other Human Milk Metabolitesmentioning
confidence: 99%
“…These metabolites are key players in human homeostasis because of their interactions with the microbiota, the immune system, and the neuroendocrine system, contributing to the immunological, metabolic, and neurological programming of the host (Stinson et al, 2020). In this context, the concentrations of acetate and butyrate in milk samples from atopic mothers are significantly lower than in samples from non-atopic mothers (Stinson et al, 2020). Levels of butyrate in milk have also been negatively associated with infant BMI and this fact may program healthy adiposity outcomes later in life (Prentice et al, 2019).…”
Section: Other Human Milk Metabolitesmentioning
confidence: 99%
“…Goat milk and cow milk have a relatively comparable total fat content and fatty acid profile [ 25 , 26 ]. SCFAs, in particular C4:0, are not always detectable or reported for human milk ( Table 1 ), however a few studies have reported levels of C4:0 in lower concentrations than in cow and goat milk fat ([ 27 , 28 ]; Table 1 ). Fat from goat milk contains a higher amount (15%–18%) of the MCFAs C6:0, C8:0 and C10:0 compared to cow milk (5%–9%) [ 26 ].…”
Section: Whole Goat Milk Fat To Supply a Variety Of Fatty Acids Anmentioning
confidence: 99%
“…There is emerging evidence of a role of fatty acids in the development of allergy in early life. For example, SCFAs, either dietary, from carbohydrate fermentation by gut bacteria or delivered via the placenta during pregnancy, have been shown in animal models and in humans to lower the risk of developing allergic and atopic diseases [ 28 ]. After absorption in the GIT, SCFAs contribute to various functions such as regulatory T cell responses and tolerance, synthesis of dendritic cell precursors in the bone marrow, and secretion of mucus and promotion of epithelial barrier integrity in the gut.…”
Section: Role Of Milk Fat and Mfgm In Infant Nutrition Growth Andmentioning
confidence: 99%
See 1 more Smart Citation